Incorporating Solid Waste Particles into Concrete Design to Enhance Drainage Infrastructure - Nadiatul Adilah, Ahmad Abdul Ghani; Fathi, Z Muhammad; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Mohd Faizal, W I Wan (IOP Publishing, 2024)
The inadequate drainage structure can cause water to accumulate on the surface of the pavement, leading to degradation and reduced lifespan of the concrete structure. This study focuses on the incorporation of solid waste particles into the concrete mix to enhance the drainage structure and other concrete structures. Solid waste particles (SWP) are added to the concrete mix to improve the strength and absorption of the concrete, thus increasing the drainage efficiency. This is an economically effective solution since solid waste particles are common and easily accessible. The study investigates the effect of different percentages of solid waste particles (0%, 5%, 10%, and 15%) on the mechanical properties of the concrete mix and its permeability. Compressive strength tests were used to determine the mechanical parameters of the concrete mixtures and water absorption test to describe the porosity and moisture sensitivity of concrete.